Four‐implant‐supported overdenture treatment in the maxilla. Part I: A randomized controlled split mouth trial assessing the effect of microthreads and abutment connection type on 4 years peri‐implant health. (11th August 2021) - Doornewaard, Ron; Sakani, Samir; Matthys, Carine; Glibert, Maarten; Bronkhorst, Ewald; Vandeweghe, Stefan; Vervaeke, Stijn; De Bruyn, Hugo
Abstract: Background: According to literature, peri‐implant bone loss is minimized on implants with microthreaded neck design and internal type of abutment connection. However, most clinical studies may be biased due to confounding factors. Purpose: This nonblinded RCT assessed the effect of implant neck (microthreaded vs non‐microthreaded) as well as the type of abutment connection (internal conical vs external flat‐to‐flat) on peri‐implant bone stability and peri‐implant health after at least 36 months. Materials and methods: Twenty‐five patients were treated with a maxillary implant‐supported bar‐retained overdenture on four different implant types: internal connection with microthreads (I‐MT), internal connection without microthreads (I‐NMT), external connection with microthreads (E‐MT), and external connection without microthreads (E‐NMT). To control confounding factors, all other design features were similar. A linear mixed‐model analysis or mixed‐model logistic regression analysis was used to determine the effect of implant type on bone level, probing pocket depth, bleeding on probing, and plaque. Results: Four out of 98 implants (4.1%) placed in 25 patients failed during provisionalization and were replaced. Mean overall bone loss after 6 months was 0.39 mm (SD 0.62, range 0.00–3.48) with limited additional bone loss of 0.04 mm (SD 0.54, range −1.80–1.63) after at least 3 years. Microthreads or connection type had no effect on the bone level, probing pocket depth, bleeding on probing, nor plaque. Conclusions: With 96% of implant survival, the maxillary overdenture supported with a bar on four implants yield a predictable outcome and the implant–abutment connection type (internal vs external) and implant neck design (microthreaded vs non‐microthreaded) have no influence on peri‐implant bone remodeling after initial bone remodeling nor up to 4 years of function. Peri‐implant bone levels are within international success standards and peri‐implant health is indicative of absence of peri‐implantitis.